Method for analyzing transmission rule of chloride ions in concrete under influence of saline invasion
By designing a high-frequency wet-dry cycle test system and regression fitting analysis of the chloride ion transport model, the problem of analysis of chloride ion transport rules in concrete under the high-frequency wet-dry alternation of salt water was solved, significantly improving the accuracy of the analysis results, and providing more reliable data support for concrete salt-proof measures.
Patent Information
- Application Number
- CN202411863147.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-17
- Publication Date
- 2025-04-25
AI Technical Summary
The existing methods cannot accurately analyze the chloride ion transport rules in concrete under the high-frequency dry and wet alternating action of brine, which affects the design and construction of salt-proof measures for concrete.
A high-frequency dry-wet cycle test system was designed. By conducting dry-wet cycle tests on concrete specimens, the high-frequency dry-wet-alternating action environment of brine was simulated, and the chloride ion concentration measurement was carried out through layer-by-layer grinding sampling and regression fitting analysis was performed in combination with the chloride ion transport model to obtain the chloride ion transport rules.
The analysis results of the chloride ion transport rules in concrete under the influence of brine invasion have been significantly improved, providing more accurate data support for formulating concrete salt-proof measures, and the method is simple and reliable, suitable for large-scale promotion and application.
Smart Images

Figure CN119880757A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of anti-salinity of concrete, in particular to a chloride ion transmission experiment in concrete, and in particular to a method for analyzing the chloride ion transmission law in concrete under the influence of salt water intrusion. Background Art
[0002] According to domestic and foreign statistics, the economic losses caused by structural corrosion and durability diseases are huge. From the 1970s to the 1980s, the economic losses caused by structural corrosion in the United States reached 70 billion to 168 billion US dollars. The 11 reinforced concrete viaducts on the central ring expressway of the Isle of England, UK, cost 28 million pounds to build, and the cost of repair due to corrosion was 45 million pounds, about 1.6 times the initial cost; in the subsequent 15 years, it continued to cost about 120 million pounds, which is close to 6 times the original project cost. Foreign scholars use the "five-fold law" to quantitatively describe the importance of considering structural durability in the design stage, that is, if $1 is saved in anti-corrosion / protection during the structural design stage, then when steel corrosion is found, remedial measures will add $5 in repair costs; when concrete cracks along the reinforcement, additional measures will add $25 in repair costs; when the structure suffers serious durability damage, additional measures will add $125 in repair costs. It can be seen that in the corrosive environment of seawater intrusion, the durability of concrete structures should be taken seriously during the design process, otherwise the economic losses caused by repairs and reinforcements during the later operation and maintenance will be difficult to predict. Before designing anti-salinity measures for concrete structures, it is also necessary to have an in-depth understanding of the chloride ion transmission laws in concrete under the influence of saltwater intrusion, so as to make targeted anti-salinity measures for concrete structures, in order to achieve better anti-salinity effects at a lower cost.
[0003] The chloride ion transmission law in concrete under the influence of salt water intrusion is generally obtained through experimental methods. In different salt water intrusion environments, the chloride ion transmission law of concrete structures is different. Therefore, for different intrusion environments, it is necessary to adjust the experimental plan in a targeted manner to accurately obtain the corresponding chloride ion transmission law. However, the existing methods for analyzing the chloride ion transmission law in concrete under the influence of salt water intrusion cannot accurately analyze the chloride ion transmission law in concrete under the high-frequency (≥5 times / day) dry-wet alternation of salt water, which seriously affects the design and construction of concrete anti-salinity measures. Summary of the invention
[0004] The purpose of the present invention is to address the problem that the existing method for analyzing the chloride ion transmission law in concrete under the influence of salt water intrusion cannot accurately analyze the chloride ion transmission law in concrete under the high-frequency dry-wet alternation of salt water, and propose a method for analyzing the chloride ion transmission law in concrete under the influence of salt water intrusion.
[0005] In order to achieve the above-mentioned object of the invention, the present invention provides a method for analyzing the chloride ion transmission law in concrete under the influence of salt water intrusion, comprising the following steps:
[0006] S1. Prepare concrete specimens, and measure the initial chloride ion diffusion coefficient of the concrete specimens and the initial chloride ion concentration in the concrete;
[0007] S2, pre-treating the concrete specimens;
[0008] S3, subjecting the pretreated concrete specimens to a dry-wet cycle test using a high-frequency dry-wet cycle test system;
[0009] S4, grinding and sampling the concrete specimens after the dry-wet cycle test layer by layer along the direction of salt water diffusion depth to obtain concrete sample powders with different exposure times and different grinding depths;
[0010] S5. After screening and drying the concrete sample powder, the chloride ion concentration in the concrete sample powder is measured;
[0011] S6. Based on the measured chloride ion concentration, the distribution of chloride ion concentration along the diffusion depth in the concrete specimen is obtained;
[0012] S7. Based on the distribution of chloride ion concentration along the diffusion depth, regression fitting analysis was performed according to the chloride ion transport model to obtain the fitting equation for the time-varying chloride ion concentration on the concrete surface, which is the chloride ion transport law in concrete under the influence of salt water intrusion.
[0013] The invention discloses a method for analyzing the transmission law of chloride ions in concrete under the influence of salt water intrusion. By specifically designing a high-frequency dry-wet cycle test system and performing a dry-wet cycle test on a concrete specimen, the intrusion environment of the concrete under the high-frequency dry-wet alternation of salt water is simulated to the greatest extent, thereby significantly improving the analysis result of the transmission law of chloride ions in concrete under the influence of salt water intrusion, providing more accurate data support for formulating concrete anti-salinity measures, and the method is simple, reliable, and suitable for large-scale promotion and application.
[0014] Among them, in step S1, preferably, the specific steps of preparing the concrete specimen include: (1) determining the raw materials and mix ratio of the concrete specimen; (2) mixing the raw materials; (3) molding and forming the mixture; and (4) curing the specimen.
[0015] Preferably, in step (1), the raw materials and mix ratio of the concrete specimen are:
[0016] Raw material types cement Fly ash Mineral powder sand gravel water Water reducing agent <![CDATA[1m 3 Amount of raw materials used for concrete (kg)]]> 189 130 72 788 1089 150 11.7
[0017] Preferably, the cement is PO.42.5 ordinary Portland cement from the same batch; the fly ash is F class I, with a fineness of 10.1% and a water requirement ratio of 93.6%; the mineral powder is S95 grade, with a 7d activity index of not less than 78%, a 28d activity index of not less than 100%, and a specific surface area of 436m 2 / kg; the sand has an apparent density of 2.61×10 3 kg / m 3 The continuous graded natural river sand; the crushed stone has an apparent density of 2.69×10 3 kg / m 3 , continuously graded natural crushed stone with a nominal particle size of 5 to 40 mm; the water reducing rate of the water reducing agent is 10% to 18%; the water is ordinary tap water.
[0018] Preferably, in step (2), the mixing time is 5-7 min and the mixing speed is 30-60 r / min.
[0019] Preferably, in step (3), the size of the concrete specimen mold is 100×100×100 mm 3 When installing the formwork, the vibration time shall comply with the provisions of the "Test Code for Concrete in Water Transport Engineering (JTJ 270-1998)".
[0020] Preferably, in step (4), the curing method comprises: first placing the undemolded concrete specimen in an environment with a temperature of 20±5°C and a relative humidity of 50% or more for initial setting curing for 24 hours, demolding the specimen after the initial setting curing is completed, and placing the demolded specimen in a saturated Ca(OH)2 solution with a temperature of 20±3°C for further curing for 28 days to obtain a concrete specimen.
[0021] Among them, in step S2, preferably, the pretreatment is to apply epoxy resin on the five non-diffusion surfaces of the concrete specimen and air-dry it to form a sealed epoxy resin layer; through the pretreatment, it can be ensured that chloride ions only invade one surface of the concrete specimen (one-dimensional corrosion).
[0022] Among them, in step S3, preferably, the high-frequency dry-wet cycle test system includes a time-controlled socket, two water pumps, mixed brine, a test box, a water storage tank and a storage table; the time-controlled socket is electrically connected to the water pump, and is used to control the water pump to circulate according to the set time; the storage table is arranged in the test box, and is used to place concrete specimens; the water storage tank is used to store mixed brine; one of the water pumps can pump the mixed brine in the water storage tank into the test box through a water pipe, and the other water pump can pump the mixed brine in the test box into the water storage tank through a water pipe.
[0023] Preferably, the storage platform is a hollow PVC pad; the storage platform can ensure that the concrete remains as dry as possible during the alternating dry and wet drying process.
[0024] Preferably, the mixed brine is a sodium chloride aqueous solution with a mass concentration of 10‰.
[0025] Preferably, in the dry-wet cycle test, the dry-wet time ratio of the concrete specimen is 1:1, and the cycle frequency is 2h / time.
[0026] Preferably, the dry-wet cycle test is conducted for 30 days, 60 days, 100 days, 150 days and 200 days.
[0027] Among them, in step S4, preferably, when grinding and sampling layer by layer, each 2 mm depth is a layer, and the number of sampling layers is not less than 10 layers.
[0028] Wherein, in step S5, preferably, the particle size of the sieved concrete sample powder is not greater than 0.63 mm.
[0029] Preferably, the drying temperature is 105±5° C. and the drying time is 1.5-2.5 h.
[0030] Preferably, the test method for the chloride ion concentration in concrete sample powder comprises: stirring and soaking a certain amount of concrete sample powder with distilled water, taking the supernatant and measuring it with a rapid chloride ion content tester; wherein the stirring time is not less than 20 minutes, and the soaking time is not less than 1 hour.
[0031] Wherein, in step S7, preferably, the chloride ion transport model is:
[0032]
[0033] Where: C0 represents the initial concentration of chloride ions in concrete (%); C s represents the chloride ion concentration on the concrete surface (%); t0 represents the initial age; t represents the exposure time; x represents the chloride ion diffusion depth (mm); C(x,t) represents the chloride ion concentration at the depth x in the concrete specimen at time t (%); D(t) represents the chloride ion diffusion coefficient at time t; n is the attenuation coefficient, erf is the error function, and D0 is the initial chloride ion diffusion coefficient.
[0034] Compared with the prior art, the present invention has the following beneficial effects:
[0035] The invention discloses a method for analyzing the transmission law of chloride ions in concrete under the influence of salt water intrusion. By specifically designing a high-frequency dry-wet cycle test system and performing a dry-wet cycle test on a concrete specimen, the intrusion environment of the concrete under the high-frequency dry-wet alternation of salt water is simulated to the greatest extent, thereby significantly improving the analysis result of the transmission law of chloride ions in concrete under the influence of salt water intrusion, providing more accurate data support for formulating concrete anti-salinity measures, and the method is simple, reliable, and suitable for large-scale promotion and application. BRIEF DESCRIPTION OF THE DRAWINGS
[0036] Figure 1 This is a mold installation photo of a concrete specimen of an embodiment of the present invention;
[0037] Figure 2 This is a curing photo of a concrete specimen of an embodiment of the present invention;
[0038] Figure 3 The graph is a distribution curve of chloride ion concentration along the diffusion depth of a concrete specimen according to an embodiment of the present invention;
[0039] Figure 4 This is a time-varying curve of chloride ion concentration on the surface of a concrete specimen according to an embodiment of the present invention. DETAILED DESCRIPTION
[0040] The present invention is further described in detail below in conjunction with the accompanying drawings and specific embodiments. However, it should not be understood that the scope of the above subject matter of the present invention is limited to the following embodiments, and all technologies realized based on the content of the present invention belong to the scope of the present invention.
[0041] Example:
[0042] A method for analyzing chloride ion transport in concrete under the influence of salt water intrusion comprises the following steps:
[0043] S1: Concrete specimen preparation;
[0044] (1) Determine the raw materials and mix ratio of concrete specimens;
[0045] The raw materials and mix ratio of concrete specimens are:
[0046] Raw material types cement Fly ash Mineral powder sand gravel water Water reducing agent <![CDATA[1m 3 Amount of raw materials used for concrete (kg)]]> 189 130 72 788 1089 150 11.7
[0047] ; Cement is PO.42.5 ordinary Portland cement from the same batch; Fly ash is Class F I, fineness 10.1%, water requirement ratio 93.6%; Mineral powder is S95, 7d activity index not less than 78%, 28d activity index not less than 100%, specific surface area 436m 2 / kg; the apparent density of sand is 2.61×10 3 kg / m 3 Continuously graded natural river sand; the crushed stone has an apparent density of 2.69×10 3 kg / m 3 , continuous graded natural crushed stone with a nominal particle size of 5 to 40 mm; the water reducing agent has a water reducing rate of 10% to 18%; the water is ordinary tap water;
[0048] (2) Mixing of raw materials;
[0049] The concrete specimens were prepared by machine mixing. The mixing process of the mixture included: wetting the inside of the concrete mixer with a wet cloth, pouring fine aggregate (river sand), fly ash, mineral powder and other raw materials into it, adding coarse aggregate (natural crushed stone) after stirring for 30 seconds, and slowly adding the water reducer and mixing water together after stirring for 2 minutes and stirring for 3 minutes. After the mixing is completed, the mixture in the mixer is poured onto the mixing board.
[0050] (3) Moulding and shaping of the mixture;
[0051] Check carefully beforehand 100×100×100mm 3 Check whether the appearance of the concrete standard plastic mold is intact, clean the inside and let it air dry; before the mixture is molded, a layer of mineral grease should be applied to the side wall and bottom of the plastic mold to facilitate the demoulding of cement mortar and concrete specimens; put the evenly mixed mixture into the plastic mold (such as Figure 1 (a)), and place the specimen and the mold (referred to as: test mold) together on a vibration table for compaction; when using a vibration table to shape the concrete specimen, the concrete mixture can be loaded into the test mold at once, and there should be a little surplus when loading; during the vibration process, the test mold should be prevented from jumping freely on the vibration table. According to the provisions of the "Test Procedures for Concrete in Water Transport Engineering (JTJ 270-1998)", the vibration time should be at least enough to make the surface slurry appear. The test mold after vibration and shaping is as follows Figure 1 (b)
[0052] (4) Maintenance of specimens;
[0053] After each molded test mold is covered with a layer of plastic film coated with mineral grease, it is then covered with a clean rag soaked in distilled water (to prevent water loss); then, the test mold is placed in a standard concrete curing box with an ambient temperature of 20±5℃ and a relative humidity of more than 50% for initial setting curing. The curing time is 24 hours. Figure 2 As shown in (a) and (b);
[0054] After the initial setting and curing, the test specimens have achieved initial strength. Take out the test mold, carefully peel off the wet rag and plastic film on its surface, and demold all the test specimens; then, immediately move the demolded test specimens into a saturated Ca(OH)2 solution at a temperature of 20±3℃ and continue to cure for 28 days (ensuring that the age of all test specimens is 28 days); after the curing is completed, the initial diffusion coefficient of chloride ions of the concrete specimens is measured (the initial diffusion coefficient measured by the natural diffusion method is 4.98×10 -12 m 2 / s) and the initial chloride ion concentration in concrete (the initial chloride ion concentration was measured by PXS-270 type chloride ion content rapid determination instrument and was 0.021%).
[0055] S2. Pre-treating the concrete specimens; the pre-treatment is to apply epoxy resin on the five non-diffusion surfaces of the concrete specimens and air-dry them to form a sealed epoxy resin layer;
[0056] S3, subjecting the pretreated concrete specimens to a dry-wet cycle test using a high-frequency dry-wet cycle test system;
[0057] The high-frequency dry-wet cycle test system includes a time-controlled socket, two water pumps, mixed brine, a test box, a water storage tank and a storage table; the time-controlled socket is electrically connected to the water pump to control the water pump to circulate according to the set time; the storage table is set in the test box for placing concrete specimens; the water storage tank is used to store mixed brine; one water pump can pump the mixed brine in the water storage tank into the test box through a water pipe, and the other water pump can pump the mixed brine in the test box into the water storage tank through a water pipe;
[0058] The storage table is a hollow PVC pad; the storage table can ensure that the concrete remains as dry as possible during the alternating dry and wet drying process;
[0059] The mixed brine is a sodium chloride aqueous solution with a mass concentration of 10‰;
[0060] In the dry-wet cycle test, the dry-wet time ratio of the concrete specimens was 1:1, and the cycle frequency was 2 h / time;
[0061] The duration of the dry-wet cycle test is 30d, 60d, 100d, 150d and 200d;
[0062] S4, grinding and sampling the concrete specimens after the dry-wet cycle test layer by layer along the direction of salt water diffusion depth to obtain concrete sample powders with different exposure times and different grinding depths;
[0063] The epoxy resin cured on the surface of various test pieces at different exposure times was peeled off, and a concrete powder sample layered grinding and collection device was used to grind and sample layer by layer starting from the remaining diffusion surface and along the diffusion depth direction. Within the depth range of 0 to 20 mm, the grinding sampling was carried out at 2 mm / layer; each layer of the ground concrete powder sample was collected and placed in a clean and transparent plastic sealing bag, and corresponding labels were made according to different exposure times and different grinding depths;
[0064] S5. After screening and drying the concrete sample powder, the chloride ion concentration in the concrete sample powder is measured;
[0065] According to the provisions of Section 7.16 of the Test Procedure for Concrete in Water Transport Engineering (JTJ 270-1998) on the determination of water-soluble chloride ion content in concrete, the ground concrete powder sample was sieved with a standard sieve with an aperture of 0.63 mm. The sieved powder sample was placed in a drying oven at a temperature of 105±5℃ for about 2 hours, and then taken out and cooled to room temperature for use;
[0066] Take out 5g of the dried powder sample with a microbalance and place it in a clean beaker. Then measure 100ml of distilled water and pour it into the beaker containing the powder. Then place the suspension on a H01-1D magnetic stirrer and stir it for 20min and let it stand for 1h. Then use a disposable syringe to take 60ml of the upper clear liquid into another clean small beaker. Use a PXS-270 chloride ion content rapid tester to measure the free chloride ion concentration in the supernatant, which is the chloride ion concentration in the concrete.
[0067] S6. Based on the measured chloride ion concentration, draw a distribution curve of chloride ion concentration of concrete specimen along the diffusion depth (such as Figure 3 As shown), the distribution of chloride ion concentration along the diffusion depth in the concrete specimen was obtained;
[0068] S7. Based on the distribution of chloride ion concentration along the diffusion depth, regression fitting analysis was performed according to the chloride ion transmission model to draw a time-varying curve of chloride ion concentration on the surface of the concrete specimen (e.g. Figure 4 As shown in the figure, the fitting equation of the time-varying chloride ion concentration on the concrete surface is obtained, which is the chloride ion transmission law in concrete under the influence of salt water intrusion;
[0069] The chloride ion transport model is:
[0070]
[0071] Where: C0 represents the initial concentration of chloride ions in concrete (%); C s represents the chloride ion concentration on the concrete surface (%); t0 represents the initial age; t represents the exposure time; x represents the chloride ion diffusion depth (mm); C(x,t) represents the chloride ion concentration at the depth x in the concrete specimen at time t (%); D(t) represents the chloride ion diffusion coefficient at time t, n is the attenuation coefficient (0.48 for ordinary cement), erf is the error function, and D0 is the initial chloride ion diffusion coefficient.
Claims
1. A method for analyzing the chloride ion transmission law in concrete under the influence of salt water intrusion, characterized in that: The following steps are involved: S1. Prepare concrete specimens, and measure the initial chloride ion diffusion coefficient of the concrete specimens and the initial chloride ion concentration in the concrete; S2, pre-treating the concrete specimens; S3, subjecting the pretreated concrete specimen to a dry-wet cycle test using a high-frequency dry-wet cycle test system; S4, grinding and sampling the concrete specimens after the dry-wet cycle test layer by layer along the direction of salt water diffusion depth to obtain concrete sample powders with different exposure times and different grinding depths; S5. After screening and drying the concrete sample powder, the chloride ion concentration in the concrete sample powder is measured; S6. Based on the measured chloride ion concentration, the distribution of chloride ion concentration along the diffusion depth in the concrete specimen is obtained; S7. Based on the distribution of chloride ion concentration along the diffusion depth, regression fitting analysis was performed according to the chloride ion transport model to obtain the fitting equation for the time-varying chloride ion concentration on the concrete surface, which is the chloride ion transport law in concrete under the influence of salt water intrusion.
2. The method for analyzing chloride ion transmission law in concrete under the influence of salt water intrusion according to claim 1 is characterized in that: In step S1, the specific steps of preparing the concrete specimen include: (1) determining the raw materials and mix ratio of the concrete specimen; (2) mixing the raw materials; (3) molding and forming the mixture; and (4) curing the specimen.
3. The method for analyzing chloride ion transmission law in concrete under the influence of salt water intrusion according to claim 2 is characterized in that: In step (1), the raw materials and mix ratio of the concrete specimen are:
4. The method for analyzing the chloride ion transmission law in concrete under the influence of salt water intrusion according to claim 2 is characterized in that: In step (4), the curing method includes: placing the undemolded concrete specimen in an environment with a temperature of 20±5°C and a relative humidity of 50% or more for initial setting curing for 24 hours, demolding the specimen after the initial setting curing is completed, and placing the demolded specimen in a saturated Ca(OH)2 solution at a temperature of 20±3°C for further curing for 28 days to obtain a concrete specimen.
5. The method for analyzing chloride ion transmission law in concrete under the influence of salt water intrusion according to claim 1 is characterized in that: In step S2, the pretreatment is to apply epoxy resin on the five non-diffusion surfaces of the concrete specimen and air-dry it to form a sealed epoxy resin layer.
6. The method for analyzing chloride ion transmission law in concrete under the influence of salt water intrusion according to claim 1 is characterized in that: In step S3, the high-frequency dry-wet cycle test system includes a time-controlled socket, two water pumps, mixed brine, a test box, a water storage tank and a storage table; the time-controlled socket is electrically connected to the water pump, and is used to control the water pump to circulate according to the set time; the storage table is arranged in the test box, and is used to place concrete specimens; the water storage tank is used to store mixed brine; one of the water pumps can pump the mixed brine in the water storage tank into the test box through a water pipe, and the other water pump can pump the mixed brine in the test box into the water storage tank through a water pipe.
7. The method for analyzing chloride ion transmission law in concrete under the influence of salt water intrusion according to claim 6 is characterized in that: The storage table is a hollow PVC pad.
8. The method for analyzing chloride ion transmission law in concrete under the influence of salt water intrusion according to claim 1 is characterized in that: In step S4, when grinding and sampling layer by layer, each 2 mm depth is considered as one layer, and the number of sampling layers is not less than 10 layers.
9. The method for analyzing chloride ion transmission law in concrete under the influence of salt water intrusion according to claim 1, characterized in that: In step S5, the particle size of the sieved concrete sample powder is no more than 0.63 mm; the drying temperature is 105±5° C., and the drying time is 1.5-2.5 h.
10. The method for analyzing chloride ion transmission law in concrete under the influence of salt water intrusion according to claim 9, characterized in that: In step S7, the chloride ion transport model is: Where: C0 represents the initial concentration of chloride ions in concrete (%); C s represents the chloride ion concentration on the concrete surface (%); t0 represents the initial age; t represents the exposure time; x represents the chloride ion diffusion depth (mm); C(x,t) represents the chloride ion concentration at the depth x in the concrete specimen at time t (%); D(t) represents the chloride ion diffusion coefficient at time t; n is the attenuation coefficient, erf is the error function, and D0 is the initial chloride ion diffusion coefficient.